Social Work Practices in the Multiethnic Urban Reality of Covid-19 in the Middle East: The Case of UAE - Elsayed, Walaa (Journal of Ethnic and Cultural Studies, 2021)
The study developed a set of universal challenges for social workers and investigated the impact thereof on social workers in the United Arab Emirates (UAE). Based on a qualitative analysis of previous research, a set of 10 universal challenges was developed. A questionnaire was created, and a survey was conducted among 304 respondents currently employed as social workers in the UAE. The survey results showed that most survey respondents selected the risk of infection as the strongest challenge. Emotional burnout, lack of reliable information, limited resources, staff capacity, problems with social distancing, lack of instructions/protocols, remote client service, and inadequate education obtained average scores meaning that they are important but not critical. Scientists and practitioners can use this set of universal challenges to investigate pandemic-related challenges for social workers in various countries and regions.